Turning on the Care Coordination Switch in Rural Primary Care: Voices From the Practices—Clinician Champions, Clinician Partners, Administrators, and Nurse Care Managers - Fagnan, Lyle J. (J Ambul Care Manage, 2011)
This study sought to understand the acceptability and feasibility of office-based nurse care management in medium to large rural primary care practices. A qualitative assessment of Care Management Plus (a focused medical home model for complex patients) implementation was conducted using semistructured interviews with 4 staff cohorts. Cohorts included clinician champions, clinician partners, practice administrators, and nurse care managers. Seven key implementation attributes were: a proven care coordination program; adequate staffing; practice buy-in; adequate time; measurement; practice facilitation; and functional information technology. Although staff was positive about the care coordination concept, model acceptability was varied and additional study is required to determine sustainability.